Penerimaan Diri Remaja Sebagai Penyandang Gangguan Bipolar - Nisrina Fauziah Irtandi; Nurliana Cipta Apsari (Politeknik Kesejahteraan Sosial Bandung, 2022)
Currently, the discussion of mental health issues is increasingly widespread in the community. Discussion about mental health feels to occur because of an increase in the number of cases of mental disorders. Bipolar disorder is one of the mental illnesses that has increased the number of cases. Moreover, bipolar disorder sufferers are dominated by the group of adolescents because of the demands and pressures when carrying out the development phase. Social workers as a relief profession can help adolescents as bipolar disorder to increase self-acceptance through social work interventions. The preparation of this research uses research methods of literature studies to search for and collect data from various written sources related to research topics. This study aims to find out the self-acceptance of a teenager who has bipolar disorder. A teenager who has bipolar disorder will be able to interact with his social environment well when he has good self-acceptance as well.